A Comprehensive Evaluation of Antibiotic Usage: Establishing a Foundation for Effective Antimicrobial Stewardship - Nurma Suri; Mirza Junando; Regi Afriyana (Universitas Airlangga, 2024)
Background: The intensive care unit (ICU) is a significant area of antibiotic use, accounting for a substantial proportion of the overall antibiotic consumption. The inappropriate use of antibiotics in such settings has a notable impact on the emergence of antimicrobial resistance. Objective: This study evaluated the rationality of antibiotic use in the ICU of RSUD Abdul Moeloek Hospital in Lampung Province. Methods: This study was conducted between December 2022 and February 2023 using a prospective method and purposive sampling. An evaluation was conducted using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) system for quantitative analysis and Gyssens criteria for qualitative assessment. The research subjects comprised 55 individuals, the majority of whom were male (58.2%), aged > 65 years (29.1%), remained in the ICU for less than seven days (78.2%), and subsequently continued their treatment in a non-ICU (69.1%). Results: Quantitative analysis demonstrated that the total number of antibiotics administered in this study was 394.83 DDD, with a DDD/100 patient-day value of 113.78. Ceftriaxone was the most frequently prescribed antibiotic (219 DDD), whereas gentamicin was the least frequently prescribed (1 DDD). Qualitative analysis revealed that 17.6% of the patients exhibited irrational antibiotic use. Conclusion: Irrational use of antibiotics was observed in the following categories: IV A (1.1%); IV D (2.2%); III A (2.2%); III B (2.2%) IIA, (3.3%); IIB (5.5%); and I (1.1%). The study concluded that there was still a considerable degree of irrational antibiotic use.